REKONSTRUKSI KOGNITIF, SOSIAL-EMOSIONAL SISWA MELALUI INTERNET POSITIF (Studi Penggunaan Internet/Smartphone pada Siswa MTs Negeri 7 Model Jakarta) - Najwaa Chadeeja Alhady; Ara Fahana Salsabila; Nazula Nur Azizah (Sosio-Didaktika: Social Science Education Journal, 2018)
This paper attempts to know the characteristics of students in using the internet/smartphone and how the of internet/smartphone influence the cognitive, social and emotional development of students. This quantitative research reveal the characteristics of internet usage among teenagers, especially regarding the length of time to access internet / smartphone, the amount of data usage and source of financing the purchase of data / pulse. The results also showed the influence of internet / smartphone usage on student achievement. Achievements in social, skills and communication subjects have greater scores compared to exact subjects (Mathematics and Science). This explains that students who use the Internet have broader insights, have foreign language skills, and are able to develop their creativity. The best use time range (ideal) is in the range of 7-11 hours per week or 1-1, 5 hours per day. While use under 7 hours per week and use of over 11 hours per week did not provide a significant effect on cognitive improvement.